Robot power! - Sisler, Celeste; Aikins, Dave; Nickelodeon (Firm); Viacom International (New York Random House, 2018)
When Crusher builds robots that go out of control and run wild in Axle City, it's up to AJ, Gabby, and Blaze to stop them
At head of title: Nickelodeon Blaze and the monster machines
Preschool-Grade 1
2
Keywords: Robots -- Juvenile fiction; Robots; Trucks -- Juvenile fiction; Trucks; Robots -- Fiction; Trucks -- Fiction; Fiction; Fiction; Juvenile works; Readers (Publications); Readers (primary)